Agricoltura paesaggistica Visioni, metodi, esperienze - Poli, Daniela (Territori, 2013)
"L'agricoltura è la prima delle arti" was born from a project, from the conscious modification of a context, using knowledge which had been shared and accumulated over time. Contemporary agriculture, the daughter of the 'green revolution', of Fordism and its crisis, turned its back on the knowledge that agriculture was able to produce not only food, but also environmental protection and aesthetic quality. The texts collected in this volume are intended to encourage reflections and practices in the various areas of territory and landscape planning and design - on the university, political, technical, professional and administrative levels - which can lead the world of agriculture to regain a central role in outlining new relationships between inhabitants and territory. In these texts, the agricultural landscape represents an opportunity to produce a context where it is pleasant to live, with an approach far from the aesthetical drift of a 'picturesque' and imaginary misunderstanding; an approach which is however careful towards a contextual aesthetic, arising within and from the rural world.